Representation across languages: biographical sociology meets translation and interpretation studies - Temple, Bogusia (Qualitative Sociology Review, 2006)
Biographical approaches are increasingly being used with people who speak and write a range of languages. Even when an account is originally spoken, the final version usually ends up written in the language used by the majority of the population. Researchers have shown that adopting a language that is not the one an account was given in may change how someone is perceived. Yet little has been written by sociologists using biographical approaches about the implications of moving accounts across languages. Researchers within translation and interpretation studies are increasingly tackling issues of representation across languages and developing concepts that can usefully be applied in biographical research. They question the assumption that accounts can be unproblematically transferred across languages and argue for strategies and concepts that “foreignise” texts and challenge the baseline of the target, usually for these writers, English language. However, these concepts bring issues of their own. In this article I examine these developments and give an example from my own cross language research that show that these concepts can begin to open up debates about meaning and representation.